The Democratic Republic of the Congo : 2001 Article IV Consultation and Discussions on Staff-Monitored Program--Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Authorities. (IMF Staff Country Reports; Country Report ;, 2001)
In recent years, the IMF has released a growing number of reports and other documents covering economic and financial developments and trends in member countries. Each report, prepared by a staff team after discussions with government officials, is published at the option of the member country.